Long-Term Follow Up of the Erectile Function of Testicular Cancer Survivors - Pallotti, Francesco; Petrozzi, Alessandra; Cargnelutti, Francesco; Radicioni, Antonio Francesco; Lenzi, Andrea; Paoli, Donatella; Lombardo, Francesco (Frontiers in Endocrinology, 2019)
The diagnosis of testicular cancer (TC) can have a considerable and persistent impact on a patient’s sexuality, especially given its location. The high prevalence of TC in young adults, and the good prognosis, explain the great interest in sexual dysfunction and its influence on post-treatment quality of life. The aim of this study was to evaluate the impact of the diagnosis and treatments (inguinal orchiectomy and chemotherapy) on sex life. For this purpose, we recruited 241 TC patients attending the Laboratory of Seminology –Sperm Bank “Loredana Gandini” for sperm cryopreservation (mean age 31.3 ± 6.9 years) and 223 cancer-free healthy men who were undergoing andrological screening (mean age 32.0 ± 7.7 years). The IIEF-15 questionnaire was administered at the baseline (post-orchiectomy, pre-chemotherapy - T0) and at 6 (T1), 12 (T2), 18 (T3), 24 (T4), 48 months (T5) and >5 years (T6, median 96 months) after chemotherapy to all patients, to evaluate the following domains: erectile function (EF), orgasmic function (OF), sexual desire (SD), intercourse satisfaction (IS) and overall satisfaction (OS). A subgroup of patients also underwent blood sex hormone analysis for further correlations with IIEF scores. At the baseline, 37.7% of patients had erectile dysfunction (EF score <26) and all IIEF domains except OF showed significantly lower scores than in controls (p <0.001). Long-term follow-up revealed persistently lower scores in TC survivors than in controls for EF, SD, IS and OS. Furthermore, most IIEF domains did not improve significantly in TC patients during the duration of the follow-up, with the exception of EF, which showed a significant improvement from T2. Finally, no significant correlation was found between hormone levels (gonadotropin and testosterone) and IIEF-15 scores. In conclusion, TC and its treatment have a significant effect on sexuality. The absence of a clear correlation with biochemical hypogonadism suggests that this may to a large extent be due to the surgical procedure itself, or to the psychological impact of a cancer diagnosis. Keywords: Testicular cancer, cancer survivors, orchiectomy, sexual function, erectile dysfunction, IIEF